Ajuste de selas na raça Mangalarga Marchador - Bárbara de Oliveira Nacif Klein (2020)
Saddle Fitting interfaces rider, saddle and the horse’s back through anatomic, physiologic and biomechanical concepts. An adjusted saddle is an utmost condition for achieving a balanced ride and to optimize horses’ kinematics, thus allowing proper muscle function, a vital requisite in achieving maximum performance and comply with animal welfare guidelines. This work aims to describe Australian-type saddles (STA) commonly used in Margalarga Marchador horses (MM) and correlate saddle panels measurements with horses’ back. Linear and angular measurements of 117 saddles were taken during the 37th MM National Exposition, and from the thoracic region of 377 MM horses during the 32o Brazilian Marcha Championship and the 38th MM National Exposition MM, using a measuring tape, a hypometer and a moulder. All four STA models more commonly used were compared to horses measurements and evaluated in their capacity to distribute weight in the Gullet area. These evaluations was made on horses back before and after exercise, using a Flir E40 thermograph in eight horses. on the back of eight horses. Eleven variables concerning saddle/horse were evaluated in six adjustment areas: (1: lenght; 2: width; 3: seat – A; 4: mean– B, 5: seat – C e 6: medial heights) within seven groups: males, females, marcha picada, marcha batida, age1, age2 e age3. All 32 post-exercises thermographic panels evaluations were classified according to a qualitative score (1 to 5) (1: Very bad; 2: Bad, 3: Acceptable; 4: Good e 5: Excellent). On all 308 saddle/horse comparisons, 99,7% did not achieve an ideal index of correspondence regarding angular and metric measurements (p<0,05). On 32 Gullet thermographic evaluations, 62,5 % were scored as 1, 25,0 % as 2 and 12,5% as 3. Results highlight flaws regarding STA fitting and its low capacity of a proper weight distribution on MM horses’ back, thus compromising their performance. A better understanding of Saddle Fitting principles and saddle manufacturing